Employers awareness towards SOCSO contributions / Mohd Fazeris Fauzi - Fauzi, Mohd Fazeris (Faculty of Business and Management, 2011)
This study is designed to identify employer’s awareness toward SOCSO contributions. Government enforcement, information and employer’s attitude are the independent variables. The dependent variable is employer’s awareness toward SOCSO contributions. The objective of this study is to determine the level of employer’s awareness toward SOCSO contribution. From this study, the level of employer’s awareness can see from government enforcement, information made by SOCSO and employer’s attitude. Three independents variable were developed and tested using Statistical Package for Social Science (SPSS) version 17.0.